Stormwater best management practices (BMPs) in Brazil: citizen viewpoints, construction costs, and ecosystem services - Sousa, Bruno José de Oliveira (2021)
Stormwater Best Management Practices (BMPs) may be a way to reduce the impacts of climate and land use and land cover change. However, there is a lack of studies regarding their application considering citizen viewpoints, their construction costs, and the reduction of flood risk. Therefore, the objective of this study is to understand how people see the use of stormwater BMPs as a form of adaptation and evaluate construction costs and runoff reduction. The first part consisted of analyzing if public participation may improve the application of stormwater BMPs. This was done by creating an online survey to investigate Brazilian citizens\' opinions about the use of stormwater BMPs and evaluating the data graphically and statistically concerning the participants\' socioeconomic characteristics. Then, the second part was an evaluation of stormwater BMPs\' construction costs and the attenuation of floods they may provide. The costs were accessed through the Brazilian National Research System of Construction Costs and Indices (SINAPI). Flood reduction, on the other hand, were analyzed in terms of runoff reduction and treatment of the impervious area. Most of the respondents supported public investment in stormwater BMPs and some socioeconomic characteristics influenced their perception. Furthermore, most of the respondents showed a willingness to apply these practices in lot scale, even if they found infrastructural techniques to be more efficient. Regarding the construction cost analysis, the values determined varied for the seven scenarios considered. The higher cost did not mean more reduction in runoff, and an infrastructure technique may be more expensive with the same efficiency as large-scale use of individual techniques. The data here provided may help the decision-making for the creation of plans to implement or incentive stormwater BMPs. In addition, it may serve as a framework for future studies.